2005
DOI: 10.1074/jbc.m503071200
|View full text |Cite
|
Sign up to set email alerts
|

AGP2 Encodes the Major Permease for High Affinity Polyamine Import in Saccharomyces cerevisiae

Abstract: Polyamines play essential functions in many aspects of cell biology. Plasma membrane transport systems for the specific uptake of polyamines exist in most eukaryotic cells but have been very recently identified at the molecular level only in the parasite Leishmania. We now report that the high affinity polyamine permease in Saccharomyces cerevisiae is identical to Agp2p, a member of the yeast amino acid transporter family that was previously identified as a carnitine transporter. Deletion of AGP2 dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 62 publications
7
82
0
Order By: Relevance
“…It has recently been reported that GAP1 (15) and AGP2 (16) can catalyze the uptake of polyamines together with amino acids in yeast. However, polyamine uptake by these proteins was greatly decreased when amino acids were present in the medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that GAP1 (15) and AGP2 (16) can catalyze the uptake of polyamines together with amino acids in yeast. However, polyamine uptake by these proteins was greatly decreased when amino acids were present in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported that GAP1, located on the plasma membrane, can catalyze the uptake of putrescine and spermidine together with the uptake of amino acids (15). Although it has been reported that AGP2 can selectively catalyze the uptake of spermidine (16), there is also a report that AGP2 functions as an amino acid permease (17). In this study, we looked for proteins that can preferentially catalyze the uptake of polyamines in S. cerevisiae.…”
mentioning
confidence: 99%
“…Significant quantities of polyamines may occur in the soil (54), plant phloem (2,13,21), and root nodules (22,23,40). Polyamine uptake has been studied in many microorganisms, including bacteria (27,34), yeasts (4,28), protozoans (26,35), and soil fungi (20,37). Polyamine uptake can be used to maintain cellular homeostasis, and uptake of polyamines by swimming P. sojae zoospores, heretofore believed to be dependent on internal stores until host contact (8,11,12), could increase zoospore survival and aid the development of the germinating cysts.…”
mentioning
confidence: 99%
“…The molecular identity of any such polyamine transporter in the parasite remains elusive. Several known polyamine transporters, such as the bacterial Pot E (Kashiwagi et al, 2000), S. cerevisiae Agp2p (Aouida et al, 2005), UGA4 (Uemura et al, 2004) and L. major LmPot1 (Haider et al, 2005) are members of the amino acid/polyamine/organocation (APC) superfamily of transporters. While preliminary investigations…”
Section: Discussionmentioning
confidence: 99%